2007
DOI: 10.1097/wnr.0b013e32819f8f3f
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate improves cue navigation in the Morris water maze in rats

Abstract: Despite its still rapidly increasing use in the treatment of the attention deficit/hyperactivity disorder, the effects of methylphenidate on behavior and learning are not yet fully understood. We have used the Morris water maze to study effects of methylphenidate (1 mg/kg) on target-oriented behavior and visuospatial learning in young rats. Although the relatively low dose of 1 mg/kg methylphenidate changed the behavior in the Morris water maze when the goal was visible, reducing times to reach the visible pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The control subjects may "catch up" to the treated subjects once their presumed fear of being on the open arms is overcome. MPD at low oral doses has been found to reduce thigmotaxis, a measure of anxiety in the Morris water maze [32]. In that study, after the first few sessions of testing, there were no differences between MPD-treatment and controls, a finding which parallels our overall results quite well.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The control subjects may "catch up" to the treated subjects once their presumed fear of being on the open arms is overcome. MPD at low oral doses has been found to reduce thigmotaxis, a measure of anxiety in the Morris water maze [32]. In that study, after the first few sessions of testing, there were no differences between MPD-treatment and controls, a finding which parallels our overall results quite well.…”
Section: Discussionsupporting
confidence: 83%
“…However, the 3mg/kg dose has been shown to decrease locomotor activity [11] when quantified in the home cage in adult male rats. Also a recent study by Zeise et al [32] found improvements on the Morris water maze following oral dosing of MPD to preadolescent rats which were not due to increased swim speed. In addition, examination of the arms entered during the first week of testing revealed that there were no significant differences between the MPD 3 group and the controls suggesting that the drug did not produce non-specific increases in activity on the maze.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Surprisingly few studies have examined the long-term effects of chronic MPH exposure on cognition using No effect on monoamine levels or patterns of c-fos expression in striatum or prefrontal cortex ; no effect on locomotor activity Lagace et al (2006) PND 20, rats 2 mg/kg i.p., 16 d 12-78 d Decreased hippocampal neurogenesis at adulthood ; increased plasma corticosterone but no effect on cell proliferation ; no effect on locomotion LeBlanc-Duchin & Taukulis (2007) PND (Scherer et al 2010 ;Zeise et al 2007 ;Zhu et al 2007) (see Table 1). Impairments in spatial reference and working memory were linked to decreased BDNF levels and increased acetylcholinesterase activity in PFC, but not hippocampus (Scherer et al 2010).…”
Section: Mph Effects On Cognitive Processesmentioning
confidence: 94%
“…Increasingly, MPH is being used both on and off-label to specifically improve long-term memory (LTM) [2][3][4]. Few studies, however, have examined MPH's ability to modulate spatial or long-term memory [5][6][7]. Rather, most research has focused on MPH-induced improvements in working memory, attention, and cognitive control [8][9][10].…”
Section: Introductionmentioning
confidence: 99%